BARRIERS TO THE IMPLEMENTATION OF GREEN SUPPLY CHAIN MANAGEMENT IN A DISTRIBUTOR OF LUBRICATING OIL - Nascimento, Anete Petrusch do; Silva, Fabiane Padilha da; Nunes, Adão Alberto Blanco; Sellitto, Miguel Afonso (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The purpose of this article is to point out what are the barriers that prevent a company belonging to the supply chain of lubricating oils to implement environmentally friendly management practices within the context of Green supply chain Management. The research method was the exploratory case study in a distributor of lubricating oils. Based on a bibliographical review, a model with five categories and forty-seven variables was built. The model was investigated in a distribution company of lubricating oils, in which four barriers were considered important: difficulties in environmental partnerships with suppliers; the high cost of environmentally friendly packaging; the high cost of disposal of hazardous wastes, and expenditure on collecting used products. The first barrier is related to difficulties in outsourcing services. The others are barriers that impact the financial performance of the operation.